External therapy of traditional Chinese medicine for treating irritable bowel syndrome with diarrhea: A systematic review and meta-analysis - Xiuxiu Wei; Xiuxiu Wei; Yongtian Wen; Yongtian Wen; Yuchen Wei; Yuchen Wei; Xu Liang; Xu Liang; Xiangxue Ma; Beihua Zhang; Xudong Tang (Frontiers in Medicine, 2022)
BackgroundIrritable bowel syndrome with diarrhea (IBS-D) is a chronic functional gastrointestinal disorder that has a significant impact on quality of life, work productivity, and healthcare resources. External therapy of traditional Chinese medicine (TCM) has positive effects on IBS-D and is simple, convenient, and low-cost. This study aimed to systematically evaluate the efficacy and safety of external therapy of TCM for IBS-D.MethodsThis study was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. The PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals (VIP), Wan Fang, and Chinese Biomedical (CBM) databases were electronically searched to collect randomized controlled trials comparing external therapy of TCM with Western medicine for IBS-D from inception to 31 December 2021. Two authors independently screened, extracted, and assessed the selected studies. The Jadad scale and Cochrane Collaboration Risk of Bias tool were used to evaluate study quality. The certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE). The meta-analysis was performed using the Review Manager software (version 5.3).ResultsTwenty-one studies involving 1,862 subjects were included. Acupuncture and moxibustion were the most commonly used external therapies. The meta-analysis showed that based on total effective rate with moderate certainty of evidence (n = 21 studies, n = 1,862 participants, RR = 1.25, 95% CI [1.2, 1.31], I2 = 0%, P < 0.00001), clinical cure rate with low certainty of evidence (n = 17 studies, n = 1,502 participants, RR = 1.66, 95% CI [1.4, 1.96], I2 = 1%, P < 0.00001), recurrence rate with very low certainty of evidence (n = 5 studies, n = 260 participants, RR = 0.44, 95% CI [0.34, 0.58], I2 = 0%, P < 0.00001), total symptom score (MD = −4.9, 95% CI [−7.34, −2.47]), and IBS severity scoring system score (IBS-SSS) with moderate certainty of evidence (MD = −52.72, 95% CI [−63.9, −41.53]), the experimental group had significant advantages compared with the control group. The sensitivity analysis further confirmed the robustness of the primary outcomes. The improvement in quality of life associated with IBS (IBS-QOL) was superior in the experimental group compared to the control group, and the difference was statistically significant; however, the clinical heterogeneity was strong. The inverted funnel plot of the included studies indicated a potential publication bias.ConclusionExternal therapy of TCM for IBS-D alleviated abdominal symptoms, improved clinical effectiveness, and reduced recurrence with great safety. However, because of the limitations of publication bias in trials, more rigorous studies with a clinical design are necessary for further verification of the outcomes.Systematic Review Registration[https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42020222993].